Technical Considerations in the Surgical Management of External Laryngotracheal Trauma: Surgical Outcomes - R, Mohd Sayuti; RLA, Raja Ahmad; L, Wan Ishlah; A, Kahairi; ZA, Asha’ari; K, Norie Azilah (IIUM Medical Journal Malaysia, 2016)
Introduction: External laryngotracheal (ELT) trauma is rarely encountered in clinical practice. In most circumstances, this injury is overlooked by the primary attending team. Surgical management of ELT trauma is complicated, because there is no established management approach for this potentially life-altering, high morbidity injury. It is important for this injury to be identified early, as any delay in surgical intervention may result in poor airway and phonatory outcomes. The aim of surgical reconstruction is to minimise the above debilitating morbidities by restoring the main laryngeal functions as much as possible. Methods: We reviewed the outcomes of six surgical interventions for ELT trauma at Tengku Ampuan Afzan Hospital from June 2007 to June 2014. Clinical presentations, computed tomography (CT) scans features, intraoperative findings, and postoperative outcomes were evaluated. Results: All patients made a good recovery in terms of phonation except for one patient who had reduced speech function. After one year, one patient was still dependent on a fenestrated tracheostomy. This article describes the surgical reconstruction techniques used to achieve these positive outcomes. Stenting is helpful to aid healing and re-epithelialisation. Conclusion: Prompt recognition and non-traumatised airway control are essential for addressing laryngotracheal trauma. Subcutaneous emphysema is an important hallmark that should alert the attending physician to the possibility of ELT trauma. Immediate surgical intervention using appropriate techniques can produce favorable patient outcomes.